Evaluation of the effectiveness of probiotic preparations in controlling toxic gases and Vibrio spp. in the culture water of pacific white shrimp Penaeus vannamei in Binh Khanh commune - Phạm, Quỳnh Anh; Nguyễn, Thị Loan; Phạm, Việt Khái; Nguyen, Thi Hong Tu; Lam, Hoang Lai; Vo, Minh Long; Nguyen, Bui Anh Thu (Hue University Journal of Science: Natural Science, 2026)
Aquaculture water polluted by organic matter and toxic gases (NH3, H2S, NO2-, etc.) negatively affects shrimp growth, thereby reducing farming productivity. Probiotics are one of the measures used to prevent and improve water quality throughout the shrimp farming process. This study applied a probiotic preparations containing Bacillus spp. and Corynebacterium variabile strains isolated from shrimp pond sludge. The preparation was applied at a concentration of 10³ CFU/ml of culture water and tested under two conditions: a 1 m³ composite tank and a 2,000 m² earthen pond with plastic lining on the banks. During the culture period, the levels of NH3, H2S, and NO2- remained below permissible limits, thus not affecting shrimp health. After 84 days of culture in the composite tanks with a stocking density of 250 shrimp per tank, the survival rate reached 86%, the average shrimp weight was 22.22 g/individual, which was higher than the control tank without probiotics. In the lined earthen pond, PL15 shrimp were stocked at a density of 250,000 shrimp/2,000 m². Shrimp cultured in ponds treated with the preparation achieved a survival rate of 80.8%, an average weight of 32.64 g/individual, and an FCR of 1.25. In addition, the density of Vibrio spp. in both the composite tanks and lined earthen ponds remained below 10³ CFU/ml.